Health profile of adolescent girls visiting obstetrics and gynecology department of tertiary care hospital - Thaker, Rajal V.; Madiya, Anuradha B.; Chaudhari, Hiral D.; Maru, Jayesh D.; Baranda, Shyama B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Gynecological problems of adolescents occupy a special space in the spectrum of gynecological disorders of all ages. In this study, an attempt has been made to review the health profile of adolescent girls visiting department of Obstetrics and Gynecology of a tertiary care hospital. Methods: This observational study was conducted at a tertiary care teaching hospital during June 2014 to May 2016. Data was collected after due permission. Results: Adolescent girls having gynecological problems were 2.3%. Mean age of menarche was 12.5 years. Anemia was present in 89(62.7%). About 72(50.7%) adolescent girls were having abnormal body mass index (BMI). Majority of girls 136(95.8%) had menstrual problems. Leucorrhoea, Pelvic Inflammatory Disease (PID), ovarian mass, urinary problems, breast problems, injury to genital tract and sexual assault were present in 42(29.6%), 24(16.9%), 20(14.1%), 13(9.2%), 12(8.5%), 4(2.8%) and 1(0.7%) respectively. Conclusions: A very small proportion of adolescent girls came to the hospital for health-related issues. Anemia was present in more than half of adolescent girls and almost half of adolescent girls were having abnormal BMI. Majority of adolescent girls had menstrual problems. Health education regarding normal physiology, various gynecological problems, importance of nutrition and exercise for adolescents is necessary.